Analysis of Da'wah Speech Acts in the Film Muhammad Al Fath - Nurjannah Nurjannah; Siti Nurhalisa (Jurnal Scientia, 2024)
This study aims to analyze the speech acts of preaching in the film "Muhammad Al-Fatih" using a qualitative descriptive approach. Data collection was conducted through observation of dialogues in the film, employing the simak method with basic techniques of eavesdropping and advanced techniques of SBLC and note-taking. The analysis focuses on identifying the forms and functions of preaching speech acts in the film. Results revealed three types of communication: top-down communication, bottom-up communication, and horizontal communication. Top-down communication occurs between leaders and subordinates, such as Sultan-Praetorian, Sultan-Prime Minister, Husband-Wife, Mother-Child, Duke Notaras, and Lord Urban. Bottom-up communication involves interactions from subordinates to leaders, such as Prime Minister-Sultan, Praetorian-Sultan, Wife-Husband, Child-Mother, and Father. Horizontal communication occurs among individuals of the same status or level, such as Sultan-Sultan, Friend-Friend, and between a merchant and Hasan. The preaching speech acts were predominantly manifested in Sultan Mehmed's proclamation of the conquest of Constantinople, with 21 locutionary acts, 8 illocutionary acts, and 21 perlocutionary identified acts. This research provides insights into the forms and functions of preaching speech acts in the context of the film "Muhammad Al-Fatih."